PENGARUH CITRA MEREK DAN PEMASARAN RELASIONAL TERHADAP KEPUASAN PELANGGAN DALAM MENINGKATKAN LOYALITAS PELANGGAN (Studi pada Pelanggan Tupperware di Kota Semarang) (Students' Journal of Economic and Management, 2016)
The purpose of this study was to analyze the influence of brand image and relationship marketing to customer satisfaction in improving customer loyalty Tupperware in Semarang. The population in this study are customers that buy Tupperware in Semarang. The sample in this study as many as 100 people. The sampling technique used purposive sampling. The analysis tool used is multiple linear regression. The results of the analysis can be concluded that: brand image positively affects customer satisfaction. Relational marketing positively affects customer satisfaction. Brand image positively affects customer loyalty. Relational marketing a positive effect on customer loyalty. Customer satisfaction has positive effect on customer loyalty. Customer satisfaction does not mediate the effect of brand image on customer loyalty. Customer satisfaction does not mediate the effect of relationship marketing on customer loyalty.Keywords:     brand image, relationship marketing, customer satisfaction and customer loyalty